Vertical Foreign Direct Investment: Make, Sell and (Not) Buy - Chrysovalantou Milliou; Joel Sandonís (Center for Economic Studies and ifo Institute (CESifo), 2016)
According to conventional wisdom, multinational firms undertake vertical FDI in order to take advantage of cross-border factor cost differences and source the inputs from abroad at better terms. Recent empirical findings though document that this is not always the case. We provide theoretical support to the latter by demonstrating that when there is transfer of intangible assets between a multinational's vertically related production plants, its parent firm can engage in vertical FDI in order to improve its cross-threat and its input sourcing terms domestically and not abroad as well as in order to exploit its intangible assets in another country. We also investigate the effects of trade liberalization and the welfare consequences of vertical FDI.
Keywords: L13; L22; L23; F12; F23; 330; international trade; vertical FDI; inputs; trade liberalization; intangible assets; two-part tariffs